Solving New Student Allocation Problem (NSAP) With Analytical Hierarchy Process (AHP) - Shahbodin, Faaizah; Wan Hassim, Wan Haniza; Shibghatullah, Abdul Samad (Sci.Int, 2014)
There are many approaches used to solve New Student Allocation Problem (NSAP).Many researchers use application of Genetic Algorithm (GA).However,the study presented in this paper applies an Analytical Hierarchy Process (AHP)technique in solving New Student Allocation Problem (NSAP) handled by Registration Unit at Ungku Omar Polytechnic.The problem is the students are allocated to their class randomly,just by using their registration number and by all means without referring to their intelligence level,knowledge,skills and also their performance.So,in this paper the researcher’s focus is on solving NSAP by using AHP to allocate students into their respective classes with minimum intelligence gap in each class and the number of students in each class does not exceed its maximum capacity.The proposed solution will be tested using real data from the Politeknik Ungku Omar to see the result.